Building the international criminal court - Schiff, Benjamin N., 1952- (Cambridge ; New York : Cambridge University Press, 2008)
"The International Criminal Court (ICC) is the first and only standing international court capable of prosecuting humanity's worst crimes: genocide, war crimes, and crimes against humanity. It faces huge obstacles. It has no police force; it pursues investigations in areas of tremendous turmoil, conflict, and death; it is charged both with trying suspects and with aiding their victims; and it seeks to combine divergent legal traditions in an entirely new international legal mechanism." "International law advocates sought to establish a standing international criminal court for more than 150 years. Other temporary single-purpose criminal tribunals, truth commissions, and special courts have come and gone, but the ICC is the only permanent inheritor of the Nuremberg legacy." "In Building the International Criminal Court, Oberlin College Professor of Politics Benjamin N. Schiff analyzes the International Criminal Court, melding historical perspective, international relations theories, and observers' insights to explain the Court's origins, creation, innovations, dynamics, and operational challenges."--Jacket.
River of justice -- Learning from the Yugoslavia and Rwanda tribunals -- The statute : Justice v. Sovereignty -- Building the court -- NGOS : advocates, assets, critics and goads -- ICC-state relations -- The first situations.
Includes bibliographical references (pages 263-291) and index.
Keywords: International Criminal Court; International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991.; International Criminal Tribunal for Rwanda; International Criminal Court; International Criminal Court; International Criminal Tribunal for Rwanda; International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991.; International criminal courts; International criminal courts; ICC -- international law -- trials -- Rwanda -- Yugoslavia; war crimes -- human rights -- violations